European Task Force on Contact Dermatitis statement on coronavirus 19 disease (COVID-19) outbreak and the risk of adverse cutaneous reactions - Balato, Anna; Ayala, Fabio; Bruze, Magnus; Crepy, Marie Noëlle; Gonçalo, Margarida; Duus Johansen, Jeanne; John, Swen Malte; Pigatto, Paolo; Raimondo, Annunziata; Rustemeyer, Thomas; Schuttelaar, Marie Louise A.; Svedman, Cecilia; et al. (Journal of the European Academy of Dermatology and Venereology, 2020)
Among the basic protective measures against COVID-19, the need to wash hands frequently and in a prolonged way using soap, and to regularly use alcohol-based hand sanitizers is well established for the whole population. Healthcare workers in general, and particularly those involved in the direct care of COVID-19 patients, have to wear personal protective equipment (PPE) daily for many hours and also accomplish general preventive measurements outside their work. Cutaneous adverse reactions can develop that need to be prevented, identified and therapeutically managed. According to the data reported by Lin et al 1, based in the experience from healthcare workers in Wuhan, adverse skin reactions were reported in 74% of responders (n=376) to a general survey. The most commonly reported types of eruptions were skin dryness or desquamation (68.6%), papules or erythema (60.4%) and maceration (52,9%).
CRIS-Team Scopus Importer:2020-05-22
Keywords: contact dermatitis; covid-19; personal protective equipment